Strukturale Beobachtungen zum Neuen Testament - Stenger, Werner, 1938- (New Testament tools and studies, 1990)
This volume is a collection of essays by the author covering a period of twenty years and the most important groups of text in the New Testament. They are connected to each other by linking the interests and stimulus of modern linguistics and literary science to traditional historical- critical methods.